Les usages des outils de gestion des effectifs par les cadres de santé : le cas de l’hôpital public - Jacob, Marc-Antoine (Journal de gestion et d économie médicales, 2024)
Expectations towards healthcare are numerous and plural (improving the quality of care, managing payroll): to manage all that goals, Management tools are all over healthcare. Among actors who use these management tools, nurse managers are responsible for a pivotal role, that is to say making cooperation easier around human resources management in an organization characterized by plural professional groups. The goal of this research is to understand how nurse managers can use management tools in public hospital. To do so, a case study has been conducted, gathering forty-two meetings, sixteen half-day’s observation and secondary data. Our results show that management tools can be used through six uses: three instrumental uses, deployed between managers or with the CARE; and three sociopolitic uses, that enable managers to gather all professional groups of hospital. We discuss these results to establish a link between accounting and human resources literatures, highlighting that management tools are resource available for nurse managers to enable them to embody their pivotal role at the crossroads of various healthcare’s professional groups.